ANALISIS NILAI-NILAI FALSAFAH JAWA DALAM BUKU PITUTUR LUHUR BUDAYA JAWA KARYA GUNAWAN SUMODININGRAT SEBAGAI SUMBER BELAJAR PADA PEMBELAJARAN IPS - Arif Widodo; Sa’dun Akbar; Sujito Sujito (Direktorat Pascasarjana Universitas PGRI Kanjuruhan Malang, 2017)
This study originated from unrest author of the erosion of understanding the values of local wisdom of the students due to the distortion values of Javanese philosophy which has implications on the deterioration of character of the nation, therefore replanting Values of Javanese Philosophy in learning is especially important in learning IPS. Prior to actualize these values first educators should get a correct understanding of the meaning contained in the philosophy of Java. Therefore in this study the researchers conducted the interpretation of the book